1982
DOI: 10.1029/jb087ib09p07787
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic‐gravitational deformation by a rectangular thrust fault in a layered Earth

Abstract: Previous papers in this series have been concerned with developing the numerical techniques required for the evaluation of vertical displacements which are the result of thrust faulting in a layered, elastic‐gravitational earth model. This paper extends these methods to the calculation of fully time‐dependent vertical surface deformation from a rectangular, dipping thrust fault in an elastic‐gravitational layer over a viscoelastic‐gravitational half space. The elastic‐gravitational solutions are used together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
169
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(184 citation statements)
references
References 18 publications
15
169
0
Order By: Relevance
“…After the gravity effect was first investigated by Rundle (1980), it was further studied by some researchers (Rundle 1982;Pollitz 1997;Wang 2005). Rundle (1982) claimed that the self-gravitating effect can be neglected. However, Wang's (2005) results indicate that the gravity effect on the coseismic deformation and post-seismic is different.…”
Section: T H E E F F E C T O F E a Rt H ' S G R Av I T Y O N C O S E mentioning
confidence: 99%
See 1 more Smart Citation
“…After the gravity effect was first investigated by Rundle (1980), it was further studied by some researchers (Rundle 1982;Pollitz 1997;Wang 2005). Rundle (1982) claimed that the self-gravitating effect can be neglected. However, Wang's (2005) results indicate that the gravity effect on the coseismic deformation and post-seismic is different.…”
Section: T H E E F F E C T O F E a Rt H ' S G R Av I T Y O N C O S E mentioning
confidence: 99%
“…Sato (1971) and Sato & Matsu'ura (1973) investigated deformations in a multilayered medium. Rundle (1982) developed the viscoelastic-gravitational dislocation model. Ma & Kusznir (1994) researched the effects of layering and gravity based on a 3-D subsurface fault displacement fields.…”
Section: Introductionmentioning
confidence: 99%
“…The edge dislocation in an elastic half-space also furnishes a representation of the deformation due to the injection of a long (measured along strike) inclined dike or sill. Clearly, the representation could be improved by using a more complicated Earth model than a uniform to the faulting problem already available for a layered half-space [Rundle, 1982;Fernandez ei al., 1996;Kusznir, 1992, 1994]. However, two-dimensional solutions such as employed here are useful because of their comparative simplicity, and one of the principal uses of the two-dimensional solutions is to improve understanding of the deformation [e.g., Savage, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…However, we hope that the results of this study will provide a means with which to evaluate hydrologic conditions after an earthquake on both spatial and temporal scales. It has been suggested that postseismic pore pressure plays a role in aftershocks [Nur and Booker, 1972] [Rundle, 1982] tends to occur over longer timescales or in narrow fault zones. Second, the dislocation method, specifying the fault slip as dislocation along certain boundaries, has been widely employed to obtain stress-strain distributions.…”
mentioning
confidence: 99%